Clinical handovers between prehospital and hospital staff: literature review. Issue 7 (1st September 2014) - Wood, Kate; Crouch, Robert; Rowland, Emma; Pope, Catherine
Abstract : Background: Clinical handover plays a vital role in patient care and has been investigated in hospital settings, but less attention has been paid to the interface between prehospital and hospital settings. This paper reviews the published research on these handovers. Methods: A computerised literature search was conducted for papers published between 2000 and 2013 using combinations of terms: 'handover', 'handoff', 'prehospital', 'ambulance', 'paramedic' and 'emergency' and citation searching. Papers were assessed and included if determined to be at least moderate quality with a primary focus on prehospital to hospital handover. Findings: 401 studies were identified, of which 21 met our inclusion criteria. These revealed concerns about communication and information transfer, and themes concerning context, environment and interprofessional relationships. It is clear that handover exchanges are complicated by chaotic and noisy environments, lack of time and resources. Poor communication is linked to behaviours such as not listening, mistrust and misunderstandings between staff. While standardisation is offered as a solution, notably in terms of the use of mnemonics (alphabetical memory aids), evidence for benefit appears inconclusive. Conclusions: This review raises concerns about handovers at the interface between prehospital and hospital settings. The quality of existing research in this area is relatively poor and further high-quality research is required to understand this important part of emergency care. We need to understand the complexity of handover better to grasp the challenges of context and interprofessional relationships before we reach for tools and techniques to standardise part of the handover process.